Reflective Creativity in Hamar Divination - Strecker, Ivo (Antropologia Pubblica, 2024)
The article gives an insight into the reflective creativity that characterises the various forms of divination found in Hamar. This is to encourage us not to abandon but rather cultivate our ability to think reflectively, analogically, symbolically or, more broadly, rhetorically in order to persuade ourselves and others of what may be the right ways to act in the critical and particularly daunting situations that we are facing now, and to which we will have to respond in the future.